An allatotropin-like neuropeptide in Mesostoma ehrenbergii (Rhabdocoela, Platyhelminthes) - Adami, Mariana Laura (2012)
Allatotropin (AT), a neuropeptide isolated on the basis of its ability to stimulate the synthesis of juvenile hormones (JHs) in insects, has also been found in other groups. In addition to this function, AT has proved to be myotropic. In the present study, we analyze its expression in the free-living turbellarian Mesostoma ehrenbergii (Platyhelminthes: Typhloplanida) and its probable functional relationship with the muscle tissue. The results show the presence of an AT-like peptide in neurons located in different regions of the body of the flatworm. The analysis of the presence of the peptide together with phalloidin labeling suggests a functional relationship between the peptide and the muscle tissue. This is particularly evident at the level of the pharynx, where the peptide induces contractions at concentrations of 10⁻¹⁴ and 10⁻¹² M, suggesting that it is actually acting as a myoregulator. Detection of AT in several groups of protostomes but apparently not in deuterostomes suggests that this peptide could be a synapomorphic feature of protostomes. Indeed, the presence of AT in organisms that do not undergo metamorphosis could suggest that it was first involved in myotropic activities, being the induction of the synthesis of JHs a secondary function.